Analysis Of High-Risk Pregnancy Factors In Pregnant Women - Adeliana; Cakrawati R Cakrawati R; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background : High-risk pregnancy is a pregnancy condition associated with a higher probability of maternal and fetus complications compared with normal pregnancy . Early identification of risk factors is essential to ensure appropriate monitoring and management. Objective : To analyze risk factors associated with high-risk pregnancy among pregnant women. Methods : This study used a retrospective case-control design . The sample consisted of 50 pregnant women divided into 25 cases of high-risk pregnancy and 25 controls of low-risk pregnancy . Participants were selected using purposive sampling. Risk factors analyzed included maternal age , parity , pregnancy interval, history of obstetric complications , anemia, hypertension , comorbidities , and nutritional status. Data were collected using observation sheets and medical records . Bivariate analysis was performed using the Chi- square test and Odds Ratio (OR), with a significance level of α=0.05. Results : The analysis showed significant associations between high-risk pregnancy and risky maternal age (OR=3.75; p=0.038), risky parity (OR=3.67; p=0.045), risky pregnancy interval (OR=4.13; p=0.025), history of obstetric complications (OR=4.57; p=0.018), anemia (OR=3.86; p=0.032), hypertension (OR=5.17; p=0.014), comorbidities (OR=3.86; p=0.032), and poor nutritional status (OR=3.33; p=0.049). Conclusion : Maternal age , parity , pregnancy interval, history of obstetric complications , anemia, hypertension , comorbidities , and nutritional status were associated with high-risk pregnancy . Early detection and continuous monitoring of risk factors are important to prevent pregnancy complications.